Turkish writers who appeared in the press of the Azerbaijan Democratic Republic 1918-1920 - ELMEDDİN (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2025)
Turkey and Azerbaijan are two friendly and brotherly countries with a common history, language and cultural heritage. In this context, the cultural interaction that has been going on for centuries has manifested itself in the field of literature, and the literary and press environments of the two countries have been enriched by mutual interactions. Especially during the period of the Azerbaijan Democratic Republic, which existed in 1918-1920, these relations became stronger, and the presence of Turkish writers in the Azerbaijani press became a remarkable phenomenon. The Azerbaijan Democratic Republic was established on May 28, 1918 and created the first parliamentary republic model in the region. Along with the formation of state traditions, the press and literature also developed in this period and became a means of expressing national identity. During these years, the press of Azerbaijan covered the socio-political processes in the country and contributed to the strengthening of foreign literary and cultural ties. During the republic period, the press of Azerbaijan played an important role in the strengthening of the national ideology, the spread of enlightenment and the spread of independence ideas. Not only local writers, but also well-known writers of Turkey published their works in newspapers and magazines published in this period. Mehmet Emin Yurdakul, Feyzullah Sajid, Rovşen Eşref Bey, Arif Irfan Gareosman, Hilal Sahir, Ibrahim Shakir, Ahmed Hikmet, Ali Suad, Ismail Hikmet are among the Turkish writers whose works were published in the Azerbaijani press at that time. Their writings served to strengthen the national consciousness in Azerbaijani society, spread the ideas of Turkishness and independence. In the works and articles of these authors, themes such as patriotism, national independence, Turkish unity, and protection of cultural heritage came to the fore. The inclusion of their writings in newspapers published during the period of the Azerbaijan Republic is an important event that shows the strengthening of literary ties between Azerbaijan and Turkey and the protection of common values. Thus, the presence of Turkish writers in the Azerbaijani press in 1918-1920 revealed not only their literary ties, but also the mutual interaction of national ideals and the freedom movement through the press. This period was not only an important stage in the cultural integration of Azerbaijan and Turkey but also formed the basis of the literary and cultural cooperation between the two countries that continues to this day.